2015
DOI: 10.3349/ymj.2015.56.4.951
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a High Fat Diet Containing Diacylglycerol on Bone in C57BL/6J Mice

Abstract: PurposeIn epidemiologic and animal studies, a high fat diet (HFD) has been shown to be associated with lower bone mineral density (BMD) and a higher risk of osteoporotic fractures. Meanwhile, consuming a HFD containing diacylglycerol (DAG) instead of triacylglycerol (TAG) is known to offer metabolically beneficial effects of reductions in body weight and abdominal fat. The purpose of this study was to investigate the effects of a HFD containing DAG (HFD-DAG) on bone in mice.Materials and MethodsFour-week-old m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…DG (31:2), a member of the family of diacylglycerols, and its beneficial effect on bone mass might be from the increased differentiation of bone marrow cells into an osteogenic instead of adipogenic lineage. [48] Several limitations in our study warrant mention. First, we did not collect the dietary habits, nutritional supplements, and other lifestyle information of the participants, which would influence the circulating metabolites as well as the BMD level.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…DG (31:2), a member of the family of diacylglycerols, and its beneficial effect on bone mass might be from the increased differentiation of bone marrow cells into an osteogenic instead of adipogenic lineage. [48] Several limitations in our study warrant mention. First, we did not collect the dietary habits, nutritional supplements, and other lifestyle information of the participants, which would influence the circulating metabolites as well as the BMD level.…”
Section: Discussionmentioning
confidence: 89%
“…DG (31:2), a member of the family of diacylglycerols, and its beneficial effect on bone mass might be from the increased differentiation of bone marrow cells into an osteogenic instead of adipogenic lineage. [48] …”
Section: Discussionmentioning
confidence: 99%
“…In our study, we examined dietary effects during growth—from weaning to adulthood (18 to 26 weeks on diet). Within this time frame, both positive and negative effects of high‐fat diet on cortical bone have been reported in male C57BL/6J mice. The main difference between these two prior studies was the use of 45% high‐fat diet with diacylglycerol enrichment in the former versus 60% lard/soybean oil in the latter .…”
Section: Discussionmentioning
confidence: 96%
“…Within this time frame, both positive and negative effects of high‐fat diet on cortical bone have been reported in male C57BL/6J mice. The main difference between these two prior studies was the use of 45% high‐fat diet with diacylglycerol enrichment in the former versus 60% lard/soybean oil in the latter . The dietary composition we used (42% milk fat) was comparable to the first study and, like that report, we demonstrated positive absolute effects of high‐fat diet on cortical bone.…”
Section: Discussionmentioning
confidence: 96%
“…Low BMD will affect the osseointegration, stability, and function of an implant [ 6 ]. However, some studies have revealed that high fat diet containing diacylglycerol mitigates high fat diet-induced bone metabolic dysfunction in mice and promotes peak bone mass in young rats [ 7 , 8 ]. Therefore, the precise effect of high fat diet, particularly for high cholesterol diet (HCD), on the bone metabolism in the jaw remains controversial.…”
Section: Introductionmentioning
confidence: 99%